2021
DOI: 10.3390/cancers14010186
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic Inflammatory Response Identifies Patients with Adverse Clinical Outcome from Immunotherapy in Hepatocellular Carcinoma

Abstract: Systemic inflammation is a hallmark of cancer, and it has a pivotal role in hepatocellular carcinoma (HCC) development and progression. We conducted a retrospective study including 362 patients receiving immune check-point inhibitors (ICIs) across three continents, evaluating the influence of neutrophiles to lymphocytes ratio (NLR), platelets to lymphocytes ratio (PLR), and prognostic nutritional index (PNI) on overall (OS), progression free survival (PFS), and radiologic responses. In our 362 patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 31 publications
2
55
2
Order By: Relevance
“…Therefore, an investigation of the predictive biomarkers of immunotherapy response is important. Recently, several studies have shown that hematological parameters can predict immunotherapy response in various cancers [27][28][29]. Nevertheless, information on the prognostic value of routine blood parameters in cervical cancer after immunotherapy is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an investigation of the predictive biomarkers of immunotherapy response is important. Recently, several studies have shown that hematological parameters can predict immunotherapy response in various cancers [27][28][29]. Nevertheless, information on the prognostic value of routine blood parameters in cervical cancer after immunotherapy is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…dNLR can provide more information than NLR because it includes monocytes and other granulocyte subsets in addition to lymphocytes; it is considered an unfavorable prognostic factor in a wide range of malignancies (19,20), whereas LDH can reflect the patient's tumor burden. Several studies have shown the correlation between dNLR and LDH and the prognosis of immunotherapy (18,(21)(22)(23), and in previous studies of nonsmall cell lung cancer, patients with a "good" LIPI score (i.e., dNLR < 3 and normal LDH) had better OS and PFS, regardless of whether they have received immunotherapy, targeted therapy, or chemotherapy (12). To our knowledge, there are no studies that have explored the relationship between the combined indicator of dNLR and LDH and the prognosis of pancreatic cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that patients with PLR > or = 300 had reduced OS (6.4 vs. 16.5 months, p < 0.0001) and PFS (1.8 vs. 3.7 months, p = 0.0006). In that study, NLR emerged as an independent prognostic factor for OS in univariate and multivariate analysis (HR 1.95, p < 0.001; HR 1.73, p = 0.002, respectively) and the PLR remained an independent prognostic factor for both OS and PFS in multivariate analysis (HR 1.60, p = 0.020; HR 1.99, p = 0.021) ( 76 ).…”
Section: Blood-based Biomarkers For Immune-based Treatment In Advance...mentioning
confidence: 94%
“…During treatment, the NLR increased rapidly in patients with hyperprogressive disease (HPD) ( 75 ). In addition, a recent study showed that patients treated with various ICIs and ICI-based combination therapies with an NLR ≥ 5 had reduced OS (7.7 vs. 17.6 months, p < 0.0001), reduced PFS (2.1 vs. 3.8 months, p = 0.025), and decreased ORR (12% vs. 22%, p = 0.034), suggesting that systemic inflammation indicated by NLR is an independent negative prognostic factor in patients with HCC undergoing ICI therapy ( 76 ).…”
Section: Blood-based Biomarkers For Immune-based Treatment In Advance...mentioning
confidence: 99%